Aliran Ilmu Kalam dan Pokok-Pokok Pikirannya Masing-Masing - Elza Putri Ayundira Cory; Mustafiyanti Mustafiyanti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The school of Kalam science and its respective main points of thought. Kalam science, or Islamic theology, is a scientific discipline that discusses Islamic beliefs using rational methods and logical argumentation. This article discusses various schools in Kalam Science and their respective main points of thought. Some of the main schools in Kalam Science include:• Mu'tazilah: Mu'tazilah believed that the human mind is capable of understanding Islamic teachings rationally and that human actions are free. • Asy'ariyah: Asy'ariyah believes that human reason needs to be assisted by revelation to understand Islamic teachings and that human actions are not completely free. • Maturidiyah: Maturidiyah believes that human reason has an important role in understanding Islamic teachings, but revelation remains the main source knowledge.• Salafiyah: Salafiyah believes that the main source of Islamic knowledge is the Koran and Hadith, and that the use of reason in understanding religion must be limited. This article explains the differences in views between these schools in various theological aspects, such as the nature of God, free will, and destiny.